Morphological characteristics of adolescent elite female handball and volleyball players - Noutsos, S. K.; Meletakos, G. P.; Bayios, A. I. (Journal of Physical Education and Sport, 2019)
The aim of the current study is to compare morphological characteristics of adolescent elite female handball and volleyball players and to investigate probable differences between them. The sample of the current study consists of athletes from women`s national handball teams (n=32, age=17.8±1.1 years, body height166.6±4.5 cm, body mass 65.0±5.4 kg) and volleyball (n=16, age=18.0±1.4 years, body height 176.5±5.7 cm, body mass 68.1±7.4 kg). The measurements included five skin folds thicknesses (biceps, triceps, subscapular, suprailiac and calf), three circumferences [calf and biceps girth (relaxed and tensed)] end two widths (femur, humerus). In the initial somatometric parameters, the athletes exhibit higher performance triceps (p<0.001), subscapular (p<0.001) skinfold (mm) and biceps girth (relaxed) (cm) while volleyball players exhibit body height (cm) (p<0.05) and humeral diameter (cm) (p<0.05). In the secondary parameters, handball players express statistically significant body mass indices (kg/m²) (p<0.05), body fat (%) (p<0.002), sum of 5 skinfold (mm) (p<0.001), while volleyball players express fat free mass (kg) (p<0.001). The handball players` somatotype is taken to be a mesomorph-endomorph (3.9-3.8-1.7) with a much greater component in endomorphy (p<0.001),mesomorphy (p<0.001), and SDM (p<0.001), while volleyball players were taken as balanced endomorph (3.3-2.6-3.1) with a much greater component of ectomorphy (p<0.001), ?a? SAM (p<0.006). In conclusion, the differences may probably be due to the specific training of the female athletes.